Beta Diversity of Antarctic and Sub-Antarctic Benthic Communities Reveals a Major Role of Stochastic Assembly Processes - Valdivia, Nelson; Garces-Vargas, José; Garrido, Ignacio; Gómez, Iván; Huovinen, Pirjo; Navarro, Nelso P; Macaya, Erasmo C; Pardo, Luis Miguel (Frontiers in Marine Science, 2021)
Community assembly is the result of both, deterministic and stochastic processes. The former encompasses niche-based local-scale mechanisms such as environmental filtering and biotic interactions; the latter includes ecological drift, probabilistic coloni This study was financially supported by FONDAP grant #15150003, Centro de Investigacion en Dinamica de Ecosistemas Marinos de Altas Latitudes (IDEAL). IgG was financially supported by doctoral scholarship #72160109 (Becas Chile) granted by the Agencia Nac FONDECYT REGULAR Proyectos de Investigación FONDAP [15150003]; Centro de Investigacion en Dinamica de Ecosistemas Marinos de Altas Latitudes (IDEAL); Agencia Nacional de investigacion y Desarrollo (ANID) [72160109]; FONDECYT [1190529, 1181300, 1201069] wos 8